Biogenic silver nanoparticles: understanding the antimicrobial mechanism using Confocal Raman Microscopy. (10th January 2020) - Estevez, María Belén; Mitchell, Scott G; Faccio, Ricardo; Alborés, Silvana
Abstract: The antimicrobial properties of silver nanoparticles (AgNPs) have made them ubiquitous in a number of real-world industrial applications; however, the antimicrobial mode of action of biogenic AgNPs is not entirely understood. The use of Raman spectroscopy can provide molecular fingerprint information on various chemical and biochemical components in complex systems like microbial cultures, without the need for any complex sample pre-treatment. Consequently, the antimicrobial mechanism of AgNPs can be inferred through morphological and compositional changes of microbial cells that are monitored via changes in Raman band profiles. Here we show the synthesis of biogenic AgNPs using the extracellular cell-free filtrates of Penicillium expansum. The antimicrobial activity of the Penicillium expansum synthesized silver nanoparticles (hereafter PeNPs) was evaluated and the interactions between the nanoparticles and Escherichia coli were studied using Transmission Electron Microscopy (TEM) and Environmental Scanning Electron Microscopy (ESEM), showing the attachment of PeNPs to the surface of the bacteria and rupture of the bacterial cell membrane. Importantly, we show how Confocal Raman Microscopy can be used as an innovative approach to study the antimicrobial mechanisms, the results of which confirm that the PeNPs induce damage to bacterial and fungal cells, resulting in critical changes to polysaccharides, lipids, proteins and nucleic acids.